Fish community in man-impacted cascade reservoirs on the Vltava River - Draštík, Vladislav (Jihočeská univerzita, 2008)
Ichtyofauna with emphasis on fish fry community was studied in cascade reservoir complex of the Vltava River. Fish spatial distribution and species composition was observed along longitudinal axis of Kamýk, Slapy, Štěchovice and Vrané reservoirs using hydroacoustic, trawling and beach seining.
Fish community in man-impacted cascade reservoirs on the Vltava River
Keywords: ichtyofauna; cascade reservoirs; fish distribution; hydroacoustics; fry fish; ecohydrology; ichtyofauna; cascade reservoirs; fish distribution; hydroacoustics; fry fish; ecohydrology